2002
DOI: 10.1103/physrevlett.89.200404
|View full text |Cite
|
Sign up to set email alerts
|

Bright Soliton Trains of Trapped Bose-Einstein Condensates

Abstract: We variationally determine the dynamics of bright soliton trains composed of harmonically trapped Bose-Einstein condensates with attractive interatomic interactions. In particular, we obtain the interaction potential between two solitons. We also discuss the formation of soliton trains due to the quantum mechanical phase fluctuations of a one-dimensional condensate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
234
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(247 citation statements)
references
References 26 publications
12
234
1
Order By: Relevance
“…In this manner, the solitary waves are predicted to be able to survive many collisions without collapse, as were observed in the JILA experiment. This is in general agreement with other work predicting that the multiple soliton-trains seen in experiment [9,11] are consistent with neighbouring solitary waves having a relative phase close to π [22,[38][39][40]72,82]. The origin, and even the true existence, of these π-phase differences is an open question, and will be discussed in Section 7.…”
Section: Stability Of Solitary Wave Collisionssupporting
confidence: 91%
See 3 more Smart Citations
“…In this manner, the solitary waves are predicted to be able to survive many collisions without collapse, as were observed in the JILA experiment. This is in general agreement with other work predicting that the multiple soliton-trains seen in experiment [9,11] are consistent with neighbouring solitary waves having a relative phase close to π [22,[38][39][40]72,82]. The origin, and even the true existence, of these π-phase differences is an open question, and will be discussed in Section 7.…”
Section: Stability Of Solitary Wave Collisionssupporting
confidence: 91%
“…In the two experiments to date that have generated multiple bright solitary waves [9,11], the observed wave dynamics (post-formation of the waves) could be well described by the mean-field GPE under the assumption that the waves featured phase differences close to π [38,72,82]. This pattern of relative phases can potentially be explained by a process of solitary wave formation through modulational instability, followed by collapse of neighbouring solitons with relative phases close to zero [22,[38][39][40].…”
Section: Beyond-mean-field Treatments and Relative Phasementioning
confidence: 87%
See 2 more Smart Citations
“…29) The experimental realization of a BEC bright soliton means that, from Eq. (27), the key parameter A = LV 0 satisfies π/2 < A < 3π/2. We have shown that double pulses with moderate separation develop into a three-soliton state if each pulse satisfies A ∼ 2.25.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%